Strategi Humas Dalam Organisasi Himpunan Mahasiswa Terhadap Masyarakat Banda Aceh Dalam Bidang Digital - Adelia Putri; Sayyid Jamalul Adil (Sadida Islamic Communications and Media Studies, 2021)
Digital communication of Public Relations in Student Organizations plays a very important role in developing harmonious relationships, one of which is between students and the community itself. However, student public relations have not maximized its function in creating, fostering and maintaining public relations. This research is a descriptive qualitative research. Data collection techniques using interviews, documentation and observation. The results showed that there were five PR strategies used, namely visiting families in the village of Blangkruen, Darussalam sub district, Banda Aceh city on a regular basis, approaching community leaders, counseling to various houses, approaching small journalists, uploading documentation of positive activities to the public. social media, providing guidance to the public regarding digital functions and how the development of the internet is also important in conditions with the Covid 19 disaster which made some activities unable to carry out as usual. There are several obstacles for the Public Relations of student associations in carrying out the strategies that have been designed, namely the lack of facilities and infrastructure and the lack of personnel on duty in the field or section of public relations.